A cognitive approach to understanding knowledge-based virtual team decision making in product design. (30th May 2007) - Qiu, Yuan-Fu; Chui, Yoon-Ping; Helander, Martin G.
Cognitive approaches to the study of how people value knowledge to make decisions may provide a sound basis for improving knowledge management, team collaboration and information technology support. However, little research has addressed the cognitive and social psychological factors within knowledge activities. This paper presents the understanding of Knowledge-based Virtual Team Decision Making (K-VTD) in product design from a cognitive perspective. A cognitive model is described by a focus that is different from that of the current design research. Meanwhile, cases are studied from a cognitive perspective to present an overview of current research and implementation in companies. Practical implications are presented and new directions are explored for future research and practice.